Volcanic Record of the Last Geomagnetic Reversal in a Lava Flow Sequence From the Azores - Ricci, Julia; Carlut, Julie; Marques, Fernando Ornelas; Hildenbrand, Anthony; Valet, Jean-Pierre (Frontiers in Earth Science, 2020)
We present paleomagnetic and geochronological data of twenty-five stacked lava flows from São Miguel Island (Azores) that were emplaced during the last geomagnetic reversal (Matuyama-Brunhes, M-B). The characteristic direction of natural remanent magnetization was isolated through alternating field and/or thermal demagnetization. From bottom to top, the directional changes display a first phase with reverse, transitional and normal directions which is followed by a second phase with transitional and normal directions. Dating by Potassium-Argon (K-Ar) of fresh separated groundmass provide ages of 768 ± 5 ka and 765 ± 5 ka (1σ) for the first and second transitional episodes, respectively. We infer that this sequence recorded the last reversal and reveal the presence of a rebound that occurred soon after the transition. The age of the transition is 5–15 kyr younger than at other volcanic localities, but in agreement with astronomical ages that were recently proposed for the transitional interval. The reversal is characterized by weak field intensity during the transition, a recovery phase and a subsequent decrease during the rebound. The two transitional virtual geomagnetic poles (VGPs) that characterize the transition are found above the South Atlantic and the North Pacific. When compared to other M-B records, no VGP is found above preferred locations.